Ferritic stainless steel sheet and its manufacturing method
By controlling the chemical composition and heat treatment conditions of magnesium alloys, the problem of insufficient medium and low temperature strength and heat resistance of magnesium alloys in the prior art is solved, and the medium and low temperature strength and heat resistance of the material are improved under low cost conditions, making it suitable for automotive exhaust systems.
Patent Information
- Application Number
- JP2021056345
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-03-30
AI Technical Summary
The prior art is difficult to provide low-cost magnesium content magnesium alloy materials with medium and low temperature strength and long-term heat resistance in automotive exhaust systems.
By controlling the chemical composition and heat treatment conditions of the magnesium alloy, we ensure that the total content of Si and Nb and the dissolved amount of Nb reach a specific ratio, while inhibiting the precipitation of the Laves phase and the depletion of Al, and improving the medium and low temperature strength and heat resistance of the material.
It realizes the improvement of the medium and low temperature strength and long-term heat resistance of magnesium alloy without increasing costs, making it suitable for the high temperature environment of automobile exhaust systems.
Smart Images

Figure 0007657085000001 
Figure 0007657085000002 
Figure 0007657085000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel sheet having excellent heat resistance and a method for producing the same. The present invention relates to a heat-resistant stainless steel sheet that is most suitable for use in automobile exhaust system components that require high-temperature strength and oxidation resistance, and in particular to a ferritic stainless steel sheet that is excellent in strength at medium-low to high temperatures and after aging, and to a method for producing the same. [Background technology]
[0002] Exhaust system components such as the exhaust manifold, front pipe, and center pipe of an automobile pass high-temperature exhaust gas emitted from the engine, so the materials that make up these exhaust system components are required to have a variety of properties, including oxidation resistance, high-temperature strength, and thermal fatigue properties.
[0003] Traditionally, cast iron was generally used for automobile exhaust system components, but stainless steel exhaust manifolds have come to be used in light of stricter exhaust gas regulations, improved engine performance, and lighter vehicle weight. Exhaust gas temperatures vary by vehicle type, and are often around 750 to 850°C in recent years, but can reach even higher temperatures. Materials with high high-temperature strength and oxidation resistance are required in environments where they will be used for long periods of time in such temperature ranges.
[0004] Among stainless steels, austenitic stainless steels have excellent heat resistance and workability. However, because of their large thermal expansion coefficient, when they are used in components that are subjected to repeated heating and cooling, such as exhaust manifolds, they are prone to thermal fatigue failure.
[0005] Ferritic stainless steel has a smaller thermal expansion coefficient than austenitic stainless steel, and therefore has excellent thermal fatigue properties. In addition, ferritic stainless steel contains almost no expensive Ni compared to austenitic stainless steel, and therefore has low material costs and is widely used. However, ferritic stainless steel has lower high-temperature strength than austenitic stainless steel, and therefore technologies have been developed to improve high-temperature strength. Furthermore, various technologies have been developed from the viewpoints of oxidation resistance, formability, manufacturability, and further cost reduction.
[0006] Ferritic stainless steels that have been developed include, for example, SUS430J1L (Nb-containing steel), Nb-Si-containing steel, and SUS444 (Nb-Mo-containing steel). These steels contain Nb, and based on the Nb content, they also contain Si and Mo to improve high-temperature strength. In response to this, a technology has been developed to improve high-temperature strength and oxidation resistance by containing Al, as in Patent Document 1.
[0007] On the other hand, in recent years, there are cases where exhaust gas temperatures rise due to the installation of turbos, and cases where exhaust gas temperatures fall in favor of lean-burn combustion. When lean-burn is the aim, an insulating structure is adopted to suppress the drop in exhaust gas temperature in order to promote catalytic reactions in exhaust gas purification parts such as converters, and in some cases, exhaust system parts are covered with insulating material. With these structural changes, high temperatures are maintained for longer periods of time than ever before. For this reason, it has become necessary to develop technology to suppress the decrease in high-temperature strength of exhaust system components during long-term aging.
[0008] In addition, there is a constant demand for reducing the cost of exhaust system components. As in Patent Document 1, the use of Al may contribute to reducing the amount of Cr added, an element that improves oxidation resistance. However, reducing Cr leads to a decrease in strength at medium to low temperatures, for example, around 200°C. Considering thermal fatigue, strength is affected over the entire range from low to high temperatures, so if the aim is to reduce the amount of Cr added by using Al, it has become necessary to develop technology to improve strength at medium to low temperatures.
[0009] Patent Document 1 describes a technique for improving the oxidation resistance, high-temperature strength, workability, and corrosion resistance of a high-Al-content ferritic stainless steel. However, Patent Document 1 does not consider the strength at medium and low temperatures or the strength after long-term aging.
[0010] Patent Document 2 describes a technique for improving the oxidation resistance and thermal fatigue properties of high-Al-content ferritic stainless steels. However, most of the stainless steels described in Patent Document 2 have a Cr content of more than 15%, and no study is made on the strength at medium and low temperatures when the Cr content is reduced. Furthermore, no study is made on the strength after long-term aging.
[0011] Patent Document 3 describes a technique for improving the oxidation resistance and high-temperature salt damage resistance of a ferritic stainless steel with a high Al content and Cr content of 16% or less. However, there is no study on the strength at medium and low temperatures or after long-term aging. In addition, the stainless steel in Patent Document 3 contains more than 2.0% of expensive W, making it a high-cost steel. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2018-168457 A [Patent Document 2] Patent No. 6123964 [Patent Document 3] Patent No. 3903853 Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a ferritic stainless steel sheet excellent in strength at medium to high temperatures and after aging, and a method for producing the same. [Means for solving the problem]
[0014] In order to solve the above problems, the present inventors have intensively studied the contents of each element in steel that affect the strength at low to high temperatures and the strength after aging for ferritic stainless steel sheets with a relatively high Al content and a relatively low Cr content. In addition, the contents of each element that are contained in steel as precipitates or dissolved in steel, which affect the strength at low to high temperatures and the strength after aging, have also been intensively studied. As a result, it has been found that the strength at low to high temperatures is affected by the total amount of Si in steel and the amount of Nb dissolved in steel. In addition, in order to suppress the decrease in strength after long-term aging, it has been found that it is important to suppress the precipitation of Laves phases, etc., as well as the consumption of Al as a strengthening element due to high-temperature oxidation. In addition, it has been found that not only the contents of each element in steel but also the contents of each element contained in steel as precipitates are important for improving these characteristics. Based on these findings, a ferritic stainless steel sheet excellent in strength at low to high temperatures and the strength after aging has been invented.
[0015] That is, the gist of the present invention, which aims to solve the above problems, is as follows. (1) The chemical composition of the steel is, in mass%, C: 0.030% or less, N: 0.030% or less, Si: 0.01% or more, 5.00% or less, Mn: 0.01% or more, 3.00% or less, P: 0.050% or less, S: 0.0100% or less, Cr: 8.0% or more, 15.0% or less, Ni: 0.001% or more, 2.00% or less, Cu: 0.001% or more, 2.00% or less, Mo: 0.001% or more, 4.00% or less, Ti: 0.050% or more, 0.400% or less, Nb: 0.001% or more, 0.80% or less, Al: more than 0.70%, less than 5.00%, V: 0.01% or more, 0.30% or less, B: 0.0001% or more, 0.0050% or less, O: 0.0050% or less, Contains the balance being Fe and impurities, A ferritic stainless steel sheet, characterized in that it satisfies the following formulas (i) and (ii): [Si]+[Nb]-[*Nb]≧0.40...Equation (i) [*Ti]-3×[*Cr]≧0.001 ··· Formula (ii) Here, the [element symbol] in formula (i) and formula (ii) indicates the content (mass%) of the element in the steel, and the [*element symbol] indicates the content (mass%) of the element in the steel contained in precipitates. (2) The chemical composition of the steel, in mass%, is C: 0.020% or less, N: 0.020% or less, Si: 0.05% or more, 1.60% or less, Mn: 0.01% or more, 1.10% or less, P: 0.040% or less, S: 0.0014% or less, Cr: 10.0% or more, 15.0% or less, Ni: 0.01% or more, 0.70% or less, Cu: 0.001% or more, 0.80% or less, Mo: 0.01% or more, 2.00% or less, Ti: 0.050% or more, 0.230% or less, Nb: more than 0.03%, less than 0.60%, Al: 1.00% or more, 3.00% or less, V: 0.01% or more, 0.20% or less, B: 0.0001% or more, 0.0050% or less, O: 0.0050% or less, Contains the balance being Fe and impurities, A ferritic stainless steel sheet characterized by satisfying the following formulas (i) to (ii): [Si]+[Nb]-[*Nb]≧0.40...Equation (i) [*Ti]-3×[*Cr]≧0.001 ··· Formula (ii) Here, the [element symbol] in formula (i) and formula (ii) indicates the content (mass%) of the element in the steel, and the [*element symbol] indicates the content (mass%) of the element in the steel contained in precipitates. (3) In mass%, replacing part of Fe, W: 0.001% or more, 0.50% or less, Y: 0.001% or more, 0.50% or less, REM: 0.001% or more, 0.50% or less, Ca: 0.0001% or more, 0.0050% or less, Zr: 0.001% or more, 0.50% or less, Hf: 0.001% or more, 1.0% or less, Sn: 0.001% or more, 1.0% or less, Mg: 0.0001% or more, 0.0050% or less, Co: 0.001% or more, 1.0% or less, Sb: 0.001% or more, 1.0% or less, Bi: 0.001% or more, 1.0% or less, Ta: 0.001% or more, 1.0% or less, Ga: 0.0001% or more, 0.50% or less, The ferritic stainless steel sheet according to (1) or (2), characterized in that it contains one or more of the following: (4) A method for producing a ferritic stainless steel sheet according to any one of (1) to (3), comprising the steps of: A steel slab having a chemical composition according to any one of (1) to (3). The hot rolling process is carried out on In that case, During the hot rolling process A method for producing a ferritic stainless steel sheet, characterized in that the ratio A / B of the time A during which the temperature of the steel is above 900°C and not exceeding 1000°C to the time B during which the temperature of the steel is at least 600°C and not exceeding 900°C is controlled so as to satisfy the following formula (x): 1.0≦A / B≦100.0...Formula (x)
[0016] In the present invention, when no lower limit is specified, it means that the content includes the unavoidable impurity level. Effect of the Invention
[0017] According to the present invention, it is possible to provide a high Al-content, low Cr ferritic stainless steel sheet which is excellent in strength at medium to high temperatures and in strength after aging, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below.
[0019] First, the reasons for limiting the chemical composition of the steel of the ferritic stainless steel sheet of the present invention will be described. Here, "%" in the chemical composition of the steel means mass %.
[0020] (C: 0.030% or less) Since C is an element that reduces high-temperature strength, oxidation resistance, and strength after long-term aging, the C content is set to 0.030% or less. In order to further suppress the deterioration of the above properties, the C content is preferably set to 0.020% or less. In consideration of formability and corrosion resistance, the C content is more preferably set to 0.015% or less. Further preferably, the C content is set to 0.010% or less. However, since an excessive reduction leads to an increase in refining costs, the C content is preferably set to 0.0001% or more. More preferably, the C content is set to 0.0010%, and further preferably, the C content is set to 0.0020% or more.
[0021] (N:0.030% or less) Like C, N is an element that reduces high-temperature strength, oxidation resistance, and strength after long-term aging, so the N content is set to 0.030% or less. In order to further suppress the deterioration of the above properties, the N content is preferably set to 0.020% or less. In consideration of formability and corrosion resistance, the N content is more preferably set to 0.015% or less. Further preferably, the N content is set to 0.010% or less. However, since an excessive reduction leads to an increase in refining costs, the N content is preferably set to 0.0001% or more. More preferably, the N content is set to 0.0010%, and further preferably, the N content is set to 0.0020% or more.
[0022] (Si: 0.01% or more, 5.00% or less) Since Si is an element contained as a deoxidizer and also improves oxidation resistance and low- to medium-temperature strength, the Si content is set to 0.01% or more. In consideration of further improving low- to medium-temperature strength, the Si content is preferably set to 0.05% or more, and more preferably set to 0.30% or more. In consideration of high-temperature salt damage resistance, the Si content is more preferably set to 0.50% or more. However, since excessive Si content leads to a decrease in workability, the Si content is set to 5.00% or less. In consideration of manufacturability and manufacturing costs, the Si content is preferably set to 1.60% or less. More preferably, it is set to 1.20% or less, and even more preferably, it is set to 0.80% or less.
[0023] (Mn: 0.01% or more, 3.00% or less) Mn is an element contained as a deoxidizer, and the Mn content is set to 0.01% or more. In consideration of refining costs, the Mn content is preferably 0.05% or more. More preferably, it is 0.10% or more, and even more preferably, it is 0.15% or more. However, an excessive Mn content leads to a decrease in oxidation resistance and promotes Al consumption during long-term aging, thereby decreasing strength, so the Mn content is set to 3.00% or less. In consideration of further suppressing the decrease in the above properties, the Mn content is preferably set to 1.10% or less. In consideration of uniform elongation, hot workability, and corrosion resistance, the Mn content is more preferably set to 0.50% or less. It is even more preferably less than 0.40%.
[0024] (P:0.050% or less) P is an impurity that is mainly mixed in from raw materials during steel refining, and as its content increases, toughness and weldability decrease, so the lower its content, the better. Therefore, the P content is set to 0.050% or less. In addition, in consideration of manufacturability and manufacturing costs, the P content is preferably set to 0.040% or less. In consideration of workability, the P content is more preferably set to 0.035% or less. Even more preferably, it is set to 0.030% or less. However, since an excessive reduction leads to an increase in refining costs, the P content is preferably set to 0.001% or more. More preferably, it is set to 0.005% or more, and even more preferably, it is set to 0.010% or more.
[0025] (S:0.0100% or less) S is an impurity that is mainly mixed in from raw materials during steel refining, and it leads to a decrease in oxidation resistance and promotes Al consumption during long-term aging, thereby decreasing strength, so the S content is set to 0.0100% or less. In order to further suppress the decrease in the above properties, the S content is preferably set to 0.0022% or less. In consideration of manufacturability, the S content is more preferably set to 0.0020% or less. In consideration of corrosion resistance and high-temperature salt damage resistance, the S content is even more preferably set to 0.0014% or less. However, since an excessive reduction leads to an increase in refining costs, the S content is preferably set to 0.0001% or more. The S content is more preferably set to 0.0003% or more.
[0026] (Cr:8.0% or more, 15.0% or less) Cr improves oxidation resistance and inhibits Al consumption during long-term aging to inhibit strength degradation, so the Cr content is set to 8.0% or more. In order to further inhibit the degradation of the above properties, the Cr content is preferably set to 10.0% or more. In consideration of corrosion resistance, the Cr content is more preferably set to 10.5% or more. More preferably, it is set to 10.7% or more. However, since an excessive Cr content leads to an increase in raw material costs, the Cr content is set to 15.0% or less. In consideration of further reduction in raw material costs and workability, the Cr content is preferably set to less than 14.0%, and more preferably, it is set to less than 12.0%.
[0027] (Ni: 0.001% or more, 2.00% or less) Ni is an element that improves corrosion resistance, and the Ni content is set to 0.001% or more. It is preferably set to 0.01% or more, and more preferably set to 0.05% or more. However, an excessive Ni content leads to an increase in raw material costs, so the Ni content is set to 2.00% or less. In consideration of further reduction in raw material costs, oxidation resistance, and workability, the Ni content is preferably set to 0.70% or less. It is more preferably set to 0.50% or less, and even more preferably set to 0.40% or less.
[0028] (Cu: 0.001% or more, 2.00% or less) Cu is an element that improves corrosion resistance, and the Cu content is set to 0.001% or more. It is preferably set to 0.005% or more, and more preferably set to 0.01% or more. However, an excessive Cu content leads to an increase in raw material costs, so the Cu content is set to 2.00% or less. In consideration of further reduction in raw material costs, oxidation resistance, and hot workability, the Cu content is preferably set to 0.80% or less. It is more preferably set to 0.30% or less, and even more preferably set to 0.20% or less.
[0029] (Mo: 0.001% or more, 4.00% or less) Mo is an element that improves high-temperature strength and oxidation resistance, and the Mo content is set to 0.001% or more. In consideration of further improvement of the above characteristics, corrosion resistance, and high-temperature salt damage resistance, the Mo content is preferably set to 0.01% or more. More preferably, it is more than 0.30%, and even more preferably, it is 0.55% or more. However, since an excessive Mo content leads to an increase in raw material costs, the Mo content is set to 4.00% or less. In consideration of further reduction in raw material costs, workability, and manufacturability, the Mo content is preferably set to 2.00% or less. More preferably, it is set to 1.20% or less, and even more preferably, it is set to less than 0.80%.
[0030] (Ti: 0.050% or more, 0.400% or less) Ti is an element that combines with C, N, and S to improve high-temperature strength and oxidation resistance and suppress the decrease in strength after long-term aging, so the Ti content is set to 0.050% or more. In consideration of corrosion resistance, intergranular corrosion resistance, and deep drawability, the Ti content is preferably set to 0.080% or more. More preferably, it is set to 0.120% or more. However, since excessive Ti content increases raw material costs, the Ti content is set to 0.400% or less. In consideration of further reduction in raw material costs, uniform elongation, hole expansion workability, and manufacturability, the Ti content is preferably set to 0.230% or less. More preferably, it is set to 0.220% or less.
[0031] (Nb: 0.001% or more, 0.80% or less) Nb is an element that improves high-temperature strength, and the Nb content is set to 0.001% or more. In consideration of further improvement of the above characteristics, corrosion resistance, and high-temperature salt damage resistance, the Nb content is preferably set to more than 0.03%. More preferably, it is set to 0.05% or more, and even more preferably, it is set to more than 0.05%. However, since excessive Nb content leads to an increase in raw material costs, the Nb content is set to 0.80% or less. In consideration of further reduction of raw material costs, uniform elongation, hole expansion workability, and manufacturability, the Nb content is preferably set to 0.60% or less. More preferably, it is set to less than 0.35%, and even more preferably, it is set to 0.25% or less.
[0032] (Al: more than 0.70%, less than 5.00%) Al is contained as a deoxidizing element and also improves high-temperature strength and oxidation resistance, and the Al content is set to more than 0.70%. In consideration of further improvement of the above characteristics and high-temperature salt damage resistance, the Al content is preferably set to 1.00% or more. More preferably, it is set to more than 1.05%, and even more preferably, it is set to more than 1.55%. However, since excessive Al content leads to an increase in raw material costs, the Al content is set to 5.00% or less. In consideration of further reduction in raw material costs and workability, manufacturability, and weldability, the Al content is preferably set to 3.00% or less. More preferably, it is set to 2.50% or less, and even more preferably, it is set to 2.30% or less.
[0033] (V: 0.01% or more, 0.30% or less) V is an element that improves high-temperature strength. Therefore, the V content is set to 0.01% or more. In consideration of corrosion resistance, the V content is preferably set to 0.02% or more. More preferably, it is set to 0.03% or more. However, excessive V content leads to a decrease in high-temperature strength and a decrease in thermal fatigue life due to coarsening of precipitates. Therefore, the V content is set to 0.30% or less. In consideration of further suppression of the decrease in the above properties and the surface properties and manufacturability of the steel surface, the V content is preferably set to 0.20% or less. More preferably, it is less than 0.15%, and even more preferably, it is set to 0.10% or less.
[0034] (B: 0.0001% or more, 0.0050% or less) B is an element that improves high-temperature strength and thermal fatigue properties. Therefore, the B content is set to 0.0001% or more, preferably 0.0002% or more, more preferably 0.0003% or more, and further preferably 0.001% or more. However, an excessive B content leads to a decrease in hot workability and a decrease in the surface properties of the steel surface. Therefore, the B content is set to 0.0050% or less. In addition, in consideration of manufacturability and formability, the B content is preferably set to 0.0030% or less, and more preferably 0.0015% or less.
[0035] (O:0.0050% or less) O is an unavoidably contained impurity, and causes surface defects due to bubbles and inclusions. It also leads to a decrease in oxidation resistance, promotes Al consumption during long-term aging, and reduces strength. Therefore, the O content is set to 0.0050% or less. In addition, in consideration of manufacturability, the O content is preferably set to 0.0040% or less. More preferably, it is set to 0.0035% or less. However, since excessive reduction of O leads to an increase in refining costs, the O content is preferably set to 0.0001% or more. More preferably, it is set to 0.0003% or more, and further preferably, it is set to 0.0005% or more. Here, the O content means the total content including oxygen dissolved in the steel and oxygen of oxides present in the steel.
[0036] In the ferritic stainless steel sheet according to the present embodiment, the balance other than the above-mentioned elements is Fe and impurities. However, elements other than the above-mentioned elements may also be contained within a range that does not impair the effects of the present embodiment. The impurities referred to here are components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes when the ferritic stainless steel according to the present invention is industrially manufactured, and are permissible within a range that does not adversely affect the present invention.
[0037] Next, the formulas (i) and (ii) will be described.
[0038] The inventors, while investigating various effects on low and medium temperature strength, discovered that the total amount of Si in steel and the amount of Nb dissolved in steel is important, and obtained formula (i). Note that [Nb]-[*Nb] in formula (i) corresponds to the amount of Nb dissolved in steel.
[0039] [Si]+[Nb]-[*Nb]≧0.40...Equation (i)
[0040] In formula (i), [element symbol] is the content (mass%) of the element in the steel, and [*element symbol] is the content (mass%) of the element contained in the precipitate in the steel. Therefore, as mentioned above, the value obtained by subtracting [*Nb] from [Nb] means the amount of Nb dissolved in the steel.
[0041] If the value of the left side of formula (i) is less than 0.40, the strength at low and medium temperatures is insufficient. Therefore, it is necessary to satisfy formula (i). Preferably, the value of the left side of formula (i) is 0.60 or more. In addition, if [Si] and [Nb] are large, it may lead to an increase in raw material costs and a decrease in processability and manufacturability, so the value of the left side of formula (i) is preferably 5.80 or less, more preferably 2.20 or less.
[0042] In addition, while examining various effects on strength after long-term aging, it was concluded that it is important to improve oxidation resistance in order to suppress the consumption of Al as a strengthening element due to high-temperature oxidation. The oxidation resistance of ferritic stainless steels with a relatively high Al content is obtained by forming Al2O3 in the steel. Cr is also an element that enhances the protective properties of Al2O3. Therefore, it is important to fix C and N as Ti carbonitrides so that Cr does not become carbonitrides. It is believed that Ti and Cr contained as precipitates in steel are their respective carbonitrides. It is also believed that precipitates other than carbonitrides can become nuclei for the formation of carbonitrides during long-term aging. From this, it was found that the balance of the contents of Ti and Cr contained as precipitates in steel is important, and formula (ii) was obtained.
[0043] [*Ti]-3×[*Cr]≧0.001 ··· Formula (ii)
[0044] In the formula (ii), the symbol * denotes the content (mass%) of the element contained in the precipitates in the steel.
[0045] If the value of the left side of formula (ii) is less than 0.001, the oxidation resistance and strength after long-term aging are significantly reduced. Therefore, it is necessary to satisfy formula (ii). Preferably, the value of the left side of formula (ii) is 0.010 or more. Also, if the value of the left side of formula (ii) is too large, the amount of Ti precipitates increases, which leads to a decrease in manufacturability and an increase in manufacturing costs, so the value of the left side of formula (ii) is preferably 0.300 or less, more preferably 0.100 or less.
[0046] Moreover, excessively reducing or increasing the amount of precipitates in the steel leads to increased production costs and unstable quality. Therefore, it is preferable that the following formulae (iii) to (v) are satisfied.
[0047] 0.001≦[*Cr]≦0.100...Equation (iii) 0.001≦[*Ti]≦0.300...Equation (iv) 0.001≦[*Nb]≦0.300...Equation (v)
[0048] However, the symbol * in the formulas (iii) to (v) represents the content (mass%) of the element contained in the precipitate in the steel. More preferably, the value of the middle part of the formula (iii) is more than 0.001 and 0.050 or less, the value of the middle part of the formula (iv) is 0.020 or more and 0.100 or less, and the value of the middle part of the formula (v) is 0.005 or more and 0.100 or less.
[0049] The content (mass %) of each element, represented by [*element symbol], contained in the precipitates in the steel is determined as follows. First, the precipitates are extracted and separated from the steel by a precipitate extraction and separation process. Next, the amount of each element in the extracted precipitates is determined. Then, the amount of each element contained in the extracted precipitates is expressed as a content rate in the steel to determine [*element symbol] (mass %).
[0050] Here, the extraction and separation process involves taking an appropriate test piece from the entire thickness of the steel plate, electrolyzing the test piece in a tetramethylammonium chloride solution, and filtering the electrolytic solution through a filter with a pore size of 0.2 μm to extract precipitates from the steel. The extracted precipitates are then dissolved, and the content of each element contained in the precipitates is determined by ICP atomic emission spectrometry (ICP: Inductively Coupled Plasma).
[0051] Furthermore, the ferritic stainless steel sheet according to this embodiment can further improve its properties by selectively containing one or more of W, Y, REM, Ca, Zr, Hf, Sn, Mg, Co, Sb, Bi, Ta, and Ga as necessary. These elements are described below. Note that these elements do not necessarily have to be contained, so the lower limit of the content of each of these elements is 0%.
[0052] (W: 0.001% or more, 0.50% or less) W is an element that improves high-temperature strength, oxidation resistance, and corrosion resistance, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.01% or more, and even more preferably, it is 0.05% or more. However, since excessive W content may lead to an increase in raw material costs and a decrease in workability, toughness, and manufacturability, it is preferable that the W content is 0.50% or less. More preferably, it is 0.40% or less, and even more preferably, it is 0.30% or less.
[0053] (Y: 0.001% or more, 0.50% or less) Y is an element that improves rust resistance, hot workability, and oxidation resistance, and is preferably contained at 0.001% or more as required. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since an excessive Y content may lead to an increase in raw material costs and a decrease in manufacturability, it is preferable that the Y content is 0.50% or less. More preferably, it is 0.20% or less, and even more preferably, it is 0.10% or less.
[0054] (REM: 0.001% or more, 0.50% or less) REM (rare earth metal) is an element that improves rust resistance, hot workability, and oxidation resistance, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since excessive REM content may lead to an increase in raw material costs and a decrease in manufacturability, it is preferable to set the REM content to 0.50% or less. More preferably, it is 0.20% or less, and even more preferably, it is 0.10% or less. REM refers to a collective term for 15 elements (lanthanoids) from scandium (Sc) and lanthanum (La) to lutetium (Lu). As REM, one of the above elements may be contained alone, or two or more may be contained. When two or more of the above elements are contained as REM, the REM content is the total content of those elements.
[0055] (Ca: 0.0001% or more, 0.0050% or less) Ca is an element that improves corrosion resistance, oxidation resistance, and manufacturability, and is preferably contained at 0.0001% or more as necessary. More preferably, it is 0.0002% or more, and even more preferably, it is 0.0003% or more. However, since excessive Ca content may also lead to a decrease in corrosion resistance and manufacturability, it is preferable that the Ca content be 0.0050% or less. More preferably, it is 0.0030% or less, and even more preferably, it is 0.0020% or less.
[0056] (Zr: 0.001% or more, 0.50% or less) Zr is an element that improves corrosion resistance, intergranular corrosion resistance, high-temperature strength, and oxidation resistance, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.01% or more, and even more preferably, it is 0.03% or more. However, since excessive Zr content may lead to an increase in raw material costs and a decrease in manufacturability, it is preferable that the Zr content is 0.50% or less. More preferably, it is 0.30% or less, and even more preferably, it is 0.20% or less.
[0057] (Hf: 0.001% or more, 1.0% or less) Hf is an element that improves corrosion resistance, intergranular corrosion resistance, high-temperature strength, and oxidation resistance, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since excessive Hf content may lead to an increase in raw material costs and a decrease in manufacturability, it is preferable that the Hf content is 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is 0.30% or less.
[0058] (Sn: 0.001% or more, 1.0% or less) Sn is an element that improves corrosion resistance and high-temperature strength, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since excessive Sn content may lead to an increase in raw material costs and a decrease in toughness and manufacturability, it is preferable that the Sn content is 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is 0.30% or less.
[0059] (Mg: 0.0001% or more, 0.0050% or less) Mg may be contained as a deoxidizing element, and is also an element that improves formability and oxidation resistance, and is preferably contained at 0.0001% or more as necessary. More preferably, it is 0.0003% or more, and even more preferably, it is 0.0005% or more. However, since excessive Mg content may cause deterioration of corrosion resistance, weldability, and surface quality, it is preferable that the Mg content is 0.0050% or less. More preferably, it is 0.0030% or less, and even more preferably, it is 0.0020% or less.
[0060] (Co: 0.001% or more, 1.0% or less) Co is an element that improves high-temperature strength, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.01% or more, and even more preferably, it is 0.03% or more. However, since an excessive Co content may lead to an increase in raw material costs and a decrease in workability, toughness, and manufacturability, it is preferable that the Co content is 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is less than 0.30%.
[0061] (Sb: 0.001% or more, 1.0% or less) Sb is an element that improves high-temperature strength, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.005% or more, and even more preferably, it is 0.01% or more. However, since an excessive Sb content may cause a decrease in weldability and toughness, it is preferable that the Sb content is 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is 0.40% or less.
[0062] (Bi:0.001% or more, 1.0% or less) Bi is an element that suppresses roping that occurs during cold rolling and improves manufacturability, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since an excessive Bi content may lead to an increase in raw material costs and a decrease in workability and hot workability, it is preferable that the Bi content be 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is 0.30% or less.
[0063] (Ta: 0.001% or more, 1.0% or less) Ta is an element that improves high-temperature strength, and is preferably contained at 0.001% or more as necessary. More preferably, it is 0.003% or more, and even more preferably, it is 0.01% or more. However, since excessive Ta content may lead to an increase in raw material costs and a decrease in toughness and manufacturability, it is preferable that the Ta content is 1.0% or less. More preferably, it is 0.50% or less, and even more preferably, it is 0.30% or less.
[0064] (Ga: 0.0001% or more, 0.50% or less) Ga is an element that improves corrosion resistance and hydrogen embrittlement resistance, and is preferably contained at 0.0001% or more as necessary. More preferably, it is 0.0003% or more, and even more preferably, it is 0.001% or more. However, since an excessive Ga content may lead to an increase in raw material costs and a decrease in manufacturability, it is preferable that the Ga content is 0.50% or less. More preferably, it is 0.30% or less, and even more preferably, it is 0.20% or less.
[0065] Next, a method for producing the ferritic stainless steel sheet according to the present embodiment will be described. The ferritic stainless steel sheet according to the present embodiment may be produced by any method, but can be produced, for example, by the following production method.
[0066] The manufacturing method of the ferritic stainless steel sheet of this embodiment can employ a general process for manufacturing ferritic stainless steel. In general, molten steel is produced in a converter or electric furnace, refined in an AOD furnace or VOD furnace, and made into a steel billet by a continuous casting method or an ingot casting method, and then the process of hot rolling-annealing the hot rolled sheet-pickling-cold rolling-finish annealing-pickling is carried out. If necessary, the annealing of the hot rolled sheet may be omitted, or the cold rolling-finish annealing-pickling may be repeated.
[0067] The conditions for each of these steps may be general conditions, for example, a hot rolling heating temperature of 1000 to 1300°C, a hot rolled sheet annealing temperature of 900 to 1200°C, and a cold rolled sheet annealing temperature of 800 to 1200°C. The manufacturing method of this embodiment only needs to satisfy the formula (x) described below, and other manufacturing conditions are not limited. Therefore, the hot rolling conditions, the presence or absence of hot rolled sheet annealing, the cold rolling conditions, the hot rolled sheet and cold rolled sheet annealing temperatures, the atmosphere, etc. can be appropriately selected.
[0068] In addition, the treatment before the final pickling may be a general treatment, for example, a mechanical treatment such as shot blasting or grinding brush, or a chemical treatment such as molten salt treatment or neutral salt electrolysis. In addition, after cold rolling and annealing, temper rolling or tension leveling may be applied. Furthermore, the product plate thickness may be selected according to the required member thickness. In addition, this steel plate may be used as a material to manufacture a welded pipe by a normal manufacturing method for stainless steel pipes for exhaust system components, such as electric resistance welding, TIG welding, or laser welding.
[0069] In order to satisfy the formulas (i) and (ii) in order to improve the strength at medium to high temperatures and the strength after aging, a steel slab having a chemical composition according to the present embodiment is The hot rolling process is carried out on In this case, the ratio A / B of the time A during which the steel temperature is above 900°C and below 1000°C to the time B during which the steel temperature is at least 600°C and below 900°C is controlled so as to satisfy the following formula (x).
[0070] 1.0≦A / B≦100.0...Formula (x)
[0071] Hot Rolling Process In the above, the longer the ratio of time A during which the temperature of the steel is above 900°C and below 1000°C, the higher the ratio of Ti precipitates in the precipitates. Hot Rolling Process It is considered that the longer the ratio of time B during which the steel temperature is 600°C or more and 900°C or less, the higher the ratio of Nb and Cr precipitates. Therefore, the value of the middle part of formula (x) is set to 1.0 or more. Preferably, the value of the middle part of formula (x) is set to 2.0 or more. Moreover, if the value of the middle part of formula (x) is too large, the amount of Ti precipitates will be excessively large and the shape of the hot-rolled sheet will become unstable, leading to a decrease in manufacturability and an increase in manufacturing costs, so the value of the middle part of formula (x) is set to 100.0 or less. Preferably, it is set to 70.0 or less.
[0072] In addition, hot rolling process If the time A during which the steel temperature is above 900°C and below 1000°C during hot rolling is too short, processThe toughness of the steel sheet after the treatment is reduced, leading to a decrease in manufacturability and an increase in production costs. Moreover, if the time A is too long, the amount of Ti precipitates becomes excessively large. Therefore, the time A is preferably set to 10 seconds or more and 300 seconds or less.
[0073] Furthermore, hot rolling process If the time B during which the temperature is between 600℃ and 900℃ is too short, process The shape of the steel sheet after hot rolling becomes unstable, leading to a decrease in manufacturability and an increase in manufacturing costs. In addition, if time B is too long, various precipitates become coarse and the hot rolling process becomes difficult. process Therefore, the time B is preferably set to 2 seconds or more and 180 seconds or less.
[0074] As described above, the ferritic stainless steel sheet of the present embodiment can improve the strength at medium to high temperatures and the strength after aging, making the ferritic stainless steel sheet of the present embodiment suitable for use as a material for automobile exhaust system members. EXAMPLES
[0075] The effects of the present invention will be made clearer by the following examples. Note that the present invention is not limited to the following examples, and can be appropriately modified and implemented without departing from the gist of the present invention.
[0076] Steels having the composition shown in Tables 1 and 2 (Invention Examples A to R and Comparative Examples a to n) were melted in a vacuum melting furnace and cast into 150 kg ingots to produce steel billets. The hot rolling process is carried out on The steel sheets were then hot-rolled to a thickness of 5.0 mm. Engineering After The steel plate is subjected to pickling process. , cold rolled to a thickness of 2.0 mm Carry out the process , final annealing The process was carried out After, pickling process The manufacturing process for the product plate involves hot rolling. processThe thermal history of the steel during hot rolling is measured, and the time A when the temperature is over 900°C and below 1000°C and the time B when the temperature is over 600°C and below 900°C are determined. The ratio A / B of the time A and B is controlled while hot rolling. process was carried out.
[0077] [Table 1]
[0078] [Table 2]
[0079] Appropriate test pieces were taken from the entire thickness of the product plate obtained, and the test pieces were electrolytically treated in a tetramethylammonium chloride solution. The electrolytic solution was filtered through a filter with a pore size of 0.2 μm to extract precipitates in the steel. The extracted precipitates were then dissolved, and the amounts of Cr, Ti, and Nb contained in the precipitates were determined by ICP emission spectroscopy (ICP: Inductively Coupled Plasma). The amounts of Cr, Ti, and Nb contained in the precipitates were expressed as their contents in the steel to determine [*Cr], [*Ti], and [*Nb].
[0080] In addition, the product sheets were subjected to initial mid-low and high temperature strength evaluations, as well as mid-low and high temperature strength evaluations after long-term aging. The high temperature tensile tests conducted to evaluate mid-low and high temperature strength were in accordance with JIS G 0567, and test pieces were cut so that the tensile direction was parallel to the rolling direction of the steel sheet, and tensile tests were conducted.
[0081] For the initial mid-low temperature and high temperature strength evaluation, 0.2% yield strength was obtained at 200℃, 500℃, 800℃, and 900℃. Those that did not meet any of the following criteria were rated as "× (poor)" for 0.2% yield strength of 180MPa or more at 200℃, 150MPa or more at 500℃, 25MPa or more at 800℃, and 10MPa or more at 900℃ were rated as "◯ (good)". Furthermore, those that met all of the following criteria were rated as "◎ (even better)".
[0082] For the evaluation of mid-low and high temperature strength after long-term aging, the product sheets were aged for 200 hours at 800°C, and then the 0.2% proof stress was determined at 200°C, 500°C, 800°C, and 900°C. If at least one of the 0.2% proof stresses at each temperature after aging for 200 hours at 800°C was less than 55% of the initial 0.2% proof stress at each temperature, it was rated as "× (poor)", if all were 55% or more and at least one was less than 65%, it was rated as "◯ (good)", and if all were 65% or more, it was rated as "◎ (even better)".
[0083] Tables 3A and 3B show the contents (mass%) of Cr, Ti, and Nb in the steel as precipitates, the values of the left sides of formulas (i) and (ii), the values of the middle sides of formula (x), the evaluation results of initial intermediate-low temperature and high temperature strengths, and the evaluation results of intermediate-low temperature and high temperature strengths after long-term aging for Inventive Examples 1 to 18 and Comparative Examples 19 to 38. The unit of "content of each element contained in the steel as precipitates" in Tables 3A and 3B is mass%.
[0084] [Table 3A]
[0085] [Table 3B]
[0086] As is clear from Tables 1 to 3B, the steel sheets having the composition specified in the present invention and satisfying formulas (i) and (ii) are superior in initial strength at intermediate to low temperatures and high temperatures, and strength at intermediate to low temperatures and high temperatures after long-term aging, compared with the steel sheets of the comparative examples. It is also clear that if formula (x) is satisfied, formulas (i) and (ii) are satisfied.
[0087] The long-term aging temperature was 800°C, at which precipitates are likely to form, but even when long-term aging was similarly performed at 200°C, 500°C, or 900°C, the initial strength ranking at intermediate to low temperatures and high temperatures and the strength ranking at intermediate to low temperatures and high temperatures after long-term aging were the same as in the case of aging heat treatment at 800°C. This suggests that the examples of the present invention exhibit excellent strength in various temperature environments.
[0088] From the above, it is clear that a steel sheet having a chemical composition specified in the present invention and satisfying formulas (i) and (ii) has excellent strength at medium to high temperatures and after long-term aging. [Industrial Applicability]
[0089] According to the present invention, it is possible to provide a ferritic stainless steel sheet suitable for use as an automobile exhaust system member, which requires strength at medium to high temperatures and strength after long-term aging. Specific applications include exhaust manifolds, converters, front pipes, center pipes, mufflers, EGR, EGR coolers, turbo parts, and fastening parts for automobile exhaust systems. The present invention can promote the spread of turbo-equipped vehicles and engine vehicles that use HCCI (homogeneous charge compression ignition) combustion, to which these parts are applied, and contribute to improving automobile fuel efficiency and reducing the environmental load.
Claims
1. The chemical composition of the steel is, in mass%, C: 0.030% or less, N: 0.030% or less, Si: 0.01% or more, 5.00% or less, Mn: 0.01% or more, 3.00% or less, P: 0.050% or less, S: 0.0100% or less, Cr: 8.0% or more, 15.0% or less, Ni: 0.001% or more, 2.00% or less, Cu: 0.001% or more, 2.00% or less, Mo: 0.001% or more, 4.00% or less, Ti: 0.050% or more, 0.400% or less, Nb: 0.001% or more, 0.80% or less, Al: more than 0.70%, less than 5.00%, V: 0.01% or more, 0.30% or less, B: 0.0001% or more, 0.0050% or less, O: 0.0050% or less, Contains The balance is Fe and impurities, A ferritic stainless steel sheet, characterized in that it satisfies the following formulas (i) and (ii): [Si]+[Nb]-[*Nb]≧0.40...Formula (i) [*Ti]-3×[*Cr]≧0.001...Formula (ii) Here, in formula (i) and formula (ii), the [element symbol] indicates the content (mass%) of the element in the steel, and the [*element symbol] indicates the content (mass%) of the element contained in precipitates in the steel.
2. The chemical composition of the steel is, in mass%, C: 0.020% or less, N: 0.020% or less, Si: 0.05% or more, 1.60% or less, Mn: 0.01% or more, 1.10% or less, P: 0.040% or less, S: 0.0014% or less, Cr: 10.0% or more, 15.0% or less, Ni: 0.01% or more, 0.70% or less, Cu: 0.001% or more, 0.80% or less, Mo: 0.01% or more, 2.00% or less, Ti: 0.050% or more, 0.230% or less, Nb: more than 0.03%, less than 0.60%, Al: 1.00% or more, 3.00% or less, V: 0.01% or more, 0.20% or less, B: 0.0001% or more, 0.0050% or less, O: 0.0050% or less, Contains The balance is Fe and impurities, A ferritic stainless steel sheet, characterized in that it satisfies the following formulas (i) and (ii): [Si]+[Nb]-[*Nb]≧0.40...Formula (i) [*Ti]-3×[*Cr]≧0.001...Formula (ii) Here, in formula (i) and formula (ii), the [element symbol] indicates the content (mass%) of the element in the steel, and the [*element symbol] indicates the content (mass%) of the element contained in precipitates in the steel.
3. In mass%, replacing a part of Fe, W: 0.001% or more, 0.50% or less, Y: 0.001% or more, 0.50% or less, REM: 0.001% or more, 0.50% or less, Ca: 0.0001% or more, 0.0050% or less, Zr: 0.001% or more, 0.50% or less, Hf: 0.001% or more, 1.0% or less, Sn: 0.001% or more, 1.0% or less, Mg: 0.0001% or more, 0.0050% or less, Co: 0.001% or more, 1.0% or less, Sb: 0.001% or more, 1.0% or less, Bi: 0.001% or more, 1.0% or less, Ta: 0.001% or more, 1.0% or less, Ga: 0.0001% or more, 0.50% or less, The ferritic stainless steel sheet according to claim 1 or 2, comprising one or more of the following:
4. A method for producing a ferritic stainless steel sheet according to any one of claims 1 to 3, 4. A method for producing a ferritic stainless steel sheet, comprising: performing a hot rolling process on a steel slab having the chemical composition according to any one of claims 1 to 3; controlling a ratio A / B of a time A during which the temperature of the steel in the hot rolling process is above 900°C and not higher than 1000°C to a time B during which the temperature of the steel in the hot rolling process is 600°C or higher and not higher than 900°C so as to satisfy the following formula (x): 1.0≦A / B≦100.0...Formula (x)
Citation Information
Patent Citations
In-piping running device
JP1986023964A
Cr-CONTAINING STEEL EXCELLENT IN THERMAL FATIGUE CHARACTERISTICS
JP2008144263A
Al-CONTAINING HEAT RESISTANT FERRITIC STAINLESS STEEL FOR FUEL CELL, AND METHOD FOR PRODUCING THE SAME
JP2010222638A
Ferritic stainless steel
JP2013100595A
Low specific gravity ferritic stainless steel sheet and manufacturing method therefor
JP2018168457A